2012
DOI: 10.1038/mi.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeae selectively suppresses the development of Th1 and Th2 cells, and enhances Th17 cell responses, through TGF-β-dependent mechanisms

Abstract: Infection with Neisseria gonorrhoeae does not induce specific immunity or immune memory. Our previous studies in a murine model of vaginal gonococcal infection showed that innate immunity governed by Th17 cells was a critical aspect of the immune response elicited by this pathogen. Herein we show that N. gonorrhoeae selectively inhibited Th1 and Th2 cells and enhanced Th17 cell development through the induction of TGF-β. Whereas Th17 responses depended on gonococcal lipooligosaccharide acting through TLR4, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 49 publications
2
85
1
Order By: Relevance
“…Another pressure may stem from the human adaptive immune system. Opa ϩ Gc proteins prevent maturation and activation of CD4 ϩ T cells and block Th1-and Th2-mediated immunity (65,66). Opa ϩ Gc engagement of CEACAM1 also leads to B cell death (67).…”
Section: Discussionmentioning
confidence: 99%
“…Another pressure may stem from the human adaptive immune system. Opa ϩ Gc proteins prevent maturation and activation of CD4 ϩ T cells and block Th1-and Th2-mediated immunity (65,66). Opa ϩ Gc engagement of CEACAM1 also leads to B cell death (67).…”
Section: Discussionmentioning
confidence: 99%
“…Etanercept (a TNF-α soluble receptor, CPGJ-pharm, China, 25 μg/ml), DB-1 (a mouse anti-rat IFN-γ monoclonal antibody, IgG1, 20 μg/ml) and α-IL-17 antibody (a rabbit anti-rat IL-17 antibody, IgG, Santa Cruz, 20 μg/ml) were administrated to T cell conditioned medium accordingly [25][26][27]. FLS were seeded in 6-well plates at a density of 10 5 /well and incubated with PPT medium or control medium for 24 h with or without the above blocker accordingly, and the isotype-matched IgG control were used as controls.…”
Section: Cytokine Blocker Treatmentmentioning
confidence: 99%
“…In general, gonococcal infection is characterized as a localized and mild disease, and gonococcal infection rarely induces protective immunity against future infection, as evidenced by repetitive infections of individuals with the same strain (20,21). We recently demonstrated that immunosuppression, or immune tolerance, elicited by gonococci was associated with the selective inhibition of Th1 and Th2 cells through the induction of TGF-b along with the enhancement of Th17 cell development in response to TLR4 signaling by LOS (22).…”
mentioning
confidence: 99%